How does the farmland management rights mortgage loan affect food security: Based on the evidence of major grain producing areas in China - Xiangyu Dong; Xiangbo Cheng; Shuiling Huang; Xuran Li; Yiru Wang (PLoS ONE, 2025)
The people are the foundation of the nation, and grain is vital for their survival. Food security is crucial for national stability and well-being. This study utilizes panel data from 1,234 counties in China’s primary grain-producing regions, covering the years 2010 to 2021, to conduct a theoretical analysis and empirical examination of the impact of farmland management rights mortgage loans (FMRML) on food security, employing a difference-in-differences (DID) model. The empirical results indicate that the pilot policy significantly enhances food security in major grain-producing areas. Moreover, the conclusions remain robust following parallel trends and placebo tests. Mechanism analysis reveals that the policy can promote food security by increasing rural mechanization and boosting financial support in rural areas. Heterogeneity analysis demonstrates that factors such as regional resource endowments, economic development levels, and farmland tenure systems can lead to varying effects of the policy on food security. This research provides valuable references and insights for global practices aimed at enhancing food security through policies enabling the mortgage of farmland management rights.